Quantitative assessment of LASSO probe assembly and long-read multiplexed cloning - Syukri Shukor; Alfred Tamayo; Lorenzo Tosi; H. Benjamin Larman; Biju Parekkadan (BMC Biotechnology, 2019)
Abstract Background Long Adapter Single-Stranded Oligonucleotide (LASSO) probes were developed as a novel tool for massively parallel cloning of kilobase-long genomic DNA sequences. LASSO dramatically improves the capture length limit of current DNA padlock probe technology from approximately 150 bps to several kbps. High-throughput LASSO capture involves the parallel assembly of thousands of probes. However, malformed probes are indiscernible from properly formed probes using gel electrophoretic techniques. Therefore, we used next-generation sequencing (NGS) to assess the efficiency of LASSO probe assembly and how it relates to the nature of DNA capture and amplification. Additionally, we introduce a simplified single target LASSO protocol using classic molecular biology techniques for qualitative and quantitative assessment of probe specificity. Results A LASSO probe library targeting 3164 unique E. coli ORFs was assembled using two different probe assembly reaction conditions with a 40-fold difference in DNA concentration. Unique probe sequences are located within the first 50 bps of the 5′ and 3′ ends, therefore we used paired-end NGS to assess probe library quality. Properly mapped read pairs, representing correctly formed probes, accounted for 10.81 and 0.65% of total reads, corresponding to ~ 80% and ~ 20% coverage of the total probe library for the lower and higher DNA concentration conditions, respectively. Subsequently, we used single-end NGS to correlate probe assembly efficiency and capture quality. Significant enrichment of LASSO targets over non-targets was only observed for captures done using probes assembled with a lower DNA concentration. Additionally, semi-quantitative polyacrylamide gel electrophoresis revealed a ~ 10-fold signal-to-noise ratio of LASSO capture in a simplified system. Conclusions These results suggest that LASSO probe coverage for target sequences is more predictive of successful capture than probe assembly depth-enrichment. Concomitantly, these results demonstrate that DNA concentration at a critical step in the probe assembly reaction significantly impacts probe formation. Additionally, we show that a simplified LASSO capture protocol coupled to PAGE (polyacrylamide gel electrophoresis) is highly specific and more amenable to small-scale LASSO approaches, such as screening novel probes and templates.